2012
DOI: 10.1111/irv.12012
|View full text |Cite
|
Sign up to set email alerts
|

Acute diesel exhaust particle exposure increases viral titre and inflammation associated with existing influenza infection, but does not exacerbate deficits in lung function

Abstract: Please cite this paper as: Larcombe et al. (2012) Acute diesel exhaust particle exposure increases viral titre and inflammation associated with existing influenza infection, but does not exacerbate deficits in lung function. Influenza and Other Respiratory Viruses DOI:10.1111/irv.12012. Background  Exposure to diesel exhaust particles (DEP) is thought to exacerbate many pre‐existing respiratory diseases, including asthma, bronchitis and chronic obstructive pulmonary disease, however, there is a paucity of data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 60 publications
(105 reference statements)
0
8
0
Order By: Relevance
“…Respiratory system impedance ( Z rs ) was measured using a wave-tube system (Hantos et al, 1992) adapted for use in small animals (Peták et al, 1997; Sly et al, 2003) and a modification of the forced oscillation technique (Sly et al, 2003; Larcombe et al, 2013). During brief apneic periods, oscillatory signals between 4 and 38 Hz were delivered via a 1-m wave-tube to tracheostomized mice.…”
Section: Methodsmentioning
confidence: 99%
“…Respiratory system impedance ( Z rs ) was measured using a wave-tube system (Hantos et al, 1992) adapted for use in small animals (Peták et al, 1997; Sly et al, 2003) and a modification of the forced oscillation technique (Sly et al, 2003; Larcombe et al, 2013). During brief apneic periods, oscillatory signals between 4 and 38 Hz were delivered via a 1-m wave-tube to tracheostomized mice.…”
Section: Methodsmentioning
confidence: 99%
“…[128][129][130][131] One study looking at DEP exposure and virus titers showed that the combination of DEP and influenza infection results in increased lung neutrophils, increased influenza virus titers, and reduced lung function compared with mice exposed to DEP or influenza alone. 131 In this study lung impairment was not significantly different between DEP/influenza-exposed vs influenza alone-exposed mice, suggesting that the virus infection exerts the most significant lung damage. In vitro studies looking at airway cells exposed to DEP and influenza virus have shown increased oxidative stress, viral replication, and virus attachment in DEP-exposed cells, 132 which may be mediated by enhanced TLR3 pathways.…”
Section: Reviewmentioning
confidence: 99%
“…Though diesel exhaust, and likely other PM 2.5 matter, alters a person's immune response, the association between DEP and virus infections in humans is not heavily documented. Several murine studies showing altered airway immune responses to virus infections resulting in increased inflammation and/or impaired lung function 128131. One study looking at DEP exposure and virus titers showed that the combination of DEP and influenza infection results in increased lung neutrophils, increased influenza virus titers, and reduced lung function compared with mice exposed to DEP or influenza alone 131.…”
Section: Particulate Matter Wildfire Smoke and Traffic-related Air Po...mentioning
confidence: 99%
“…The 100 μg dose was chosen based on our previous dose-response data (Zosky et al, 2014a) and prior work on diesel particles (Boylen et al, 2011;Larcombe et al, 2013) showing that particle loads in macrophages are equivalent to those observed in human macrophages (Kulkarni et al, 2006). Control mice received 50 μL of saline alone.…”
Section: In Vivo Exposure Modelmentioning
confidence: 99%